1995
DOI: 10.1093/nar/23.10.1800
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines alter sequence-specific DNA-protein interactions

Abstract: The polyamines are abundant biogenic cations implicated in many biological processes. Despite a plethora of evidence on polyamine-induced DNA conformational changes, no thorough study of their effects on the activities of sequence-specific DNA binding proteins has been performed. We describe the in vitro effects of polyamines on the activities of purified, representative DNA-binding proteins, and on complex protein mixtures. Polyamines at physiological concentrations enhance the binding of several proteins to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 81 publications
1
77
0
5
Order By: Relevance
“…Pera et al (1986), found that putrescine, spermidine, and spermine concentrations in leukemic cells to be 0.47, 5.92 and 2.23 mM, respectively, although plasma concentration were in the range of 0.4 ± 1.5 mM (Delzenne et al, 2000). Based on these considerations and previous studies (Panagiotidis et al, 1995), we conducted the present series of experiments using 0.1 ± 2 mM concentrations of natural polyamines. Figure 2A shows the results of a representative electrophoretic mobility shift assay (EMSA) in which human recombinant ERa was incubated with 32 Plabeled ERE in the presence of increasing concentrations of spermine.…”
Section: Effect Of Polyamines On Er-ere and Nf-kb-nre Bindingmentioning
confidence: 78%
“…Pera et al (1986), found that putrescine, spermidine, and spermine concentrations in leukemic cells to be 0.47, 5.92 and 2.23 mM, respectively, although plasma concentration were in the range of 0.4 ± 1.5 mM (Delzenne et al, 2000). Based on these considerations and previous studies (Panagiotidis et al, 1995), we conducted the present series of experiments using 0.1 ± 2 mM concentrations of natural polyamines. Figure 2A shows the results of a representative electrophoretic mobility shift assay (EMSA) in which human recombinant ERa was incubated with 32 Plabeled ERE in the presence of increasing concentrations of spermine.…”
Section: Effect Of Polyamines On Er-ere and Nf-kb-nre Bindingmentioning
confidence: 78%
“…Finally, some systems require specific co-factors for correct function. Examples include cAMP for the E. coli CAP protein 67 , ATP for recombinases such as E. coli RecA or human Rad51 68, 69 and polyamines for some eukaryotic transcription factors 70 . Where necessary, small-molecule additives that stabilize complexes can be included in binding and gel buffers, to stabilize complexes during electrophoresis 3,7 .…”
Section: Strategic Considerations That Are Relevant To Emsamentioning
confidence: 99%
“…Benzoyl chloride was purchased from Merck Schuchardt (Germany) and [1,[4][5][6][7][8][9][10][11][12][13][14] C]putrescine dihydrochloride (110 mCi/mmol) was obtained from NEN Life Science Products, Inc. (Boston, MA, USA). DFMO was a gift from the Merrell Dow Research Institute (Cincinnati, OH, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…Cells were collected by centrifugation (3000Ug, 10 min) and resuspended in fresh SDM-79 medium at a concentration of 2U10 8 parasites/ml with or without the addition of CHA. [1,[4][5][6][7][8][9][10][11][12][13][14] C]Putrescine (0.3 WCi/ml) was added and after incubation for 24^60 h at 28³C, parasites were sedimented, washed with PBS and resuspended in 100 Wl of 0.2 M perchloric acid. Cell extracts were neutralized with KOH and precipitates discarded after centrifugation.…”
Section: In Vivo Labeling With Radioactive Putrescinementioning
confidence: 99%